2007
DOI: 10.1016/j.physletb.2007.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Chiral phase transition in an extended NJL model with higher-order multi-quark interactions

Abstract: The chiral phase transition and color superconductivity in an extended NJL model with eight-quark interactions are studied. The scalar-type nonlinear term hastens the chiral phase transition, the scalar-vector mixing term suppresses effects of the vector-type linear term and the scalar-diquark mixing term makes the coexisting phase wider.Quantum Chromodynamics (QCD) has non-perturbative properties. First-principle lattice QCD simulations are useful to study thermal systems at zero or small density [1,2]. At hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
122
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 35 publications
3
122
0
Order By: Relevance
“…In this work we use the parameter set of Kashiwa et al (2007), g 20 = 2.104, g 40 = 3.069, m = 5.5 MeV, and Λ = 631.5 MeV. Furthermore, the vector channel strengths are quantified by the ratios…”
Section: Njl Model With 8-quark Interactionsmentioning
confidence: 99%
“…In this work we use the parameter set of Kashiwa et al (2007), g 20 = 2.104, g 40 = 3.069, m = 5.5 MeV, and Λ = 631.5 MeV. Furthermore, the vector channel strengths are quantified by the ratios…”
Section: Njl Model With 8-quark Interactionsmentioning
confidence: 99%
“…We MeV and the sigma meson mass M σ = 600 MeV (650 MeV) [10]. It should be noted that larger G s8 yields smaller M σ .…”
mentioning
confidence: 93%
“…Meanwhile, it was recently reported that the vector type interaction [10,23,24,25] is necessary to realize the heavy neutron star [26]. This may indicate that the vector type interaction is necessary in the finite µ region of the phase diagram.…”
mentioning
confidence: 99%
See 2 more Smart Citations